2000
DOI: 10.3314/jjmm.41.263
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Tinea Corporis by Infection from a Rabbit with Arthroderma benhamiae.

Abstract: The first cases of tinea corporis with Arthroderma benhamiae in Japan are reported. A 7-year-old girl and a 30-year-old mother in Shimane prefecture suffered from dermatophyte infections on the neck, shoulder, arms and leg. Three isolates from the two patients and a rabbit by which they supposedly were infected, were identified as Trichophyton mentagrophytes. On the bases of mating tests using the tester strains of both the African race and the Americano-European race of A, benhamiae, they were identified as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 6 publications
0
12
0
4
Order By: Relevance
“…The species was not isolated in Japan in an intensive mating study performed in 1980 (3), and the first reported case in Japan was a dermatophytosis on a rabbit in 1997 (4). After that, several cases of dermatophytoses on humans have been reported, but all these cases were infected by pet animals (57). We report a Japanese patient with A. benhamiae infection who had no contact with any infected animals but became infected while conducting research on this dermatophyte.…”
Section: Introductionmentioning
confidence: 99%
“…The species was not isolated in Japan in an intensive mating study performed in 1980 (3), and the first reported case in Japan was a dermatophytosis on a rabbit in 1997 (4). After that, several cases of dermatophytoses on humans have been reported, but all these cases were infected by pet animals (57). We report a Japanese patient with A. benhamiae infection who had no contact with any infected animals but became infected while conducting research on this dermatophyte.…”
Section: Introductionmentioning
confidence: 99%
“…The present molecular epidemiological study showed consistency in the NTS types between the strains isolated from different lesions in the same patients, between the strains isolated from members of the same family, and between the strains isolated from pets and their owners (Table 1). For example, strains isolated from an owner (KMU4136) (6) and from her pet rabbit (KMU4137) (6) were of the NTS1 type, and 2 strains isolated from different lesions in 1 patient (KMU4169 and KMU4170) (19) were of the NTS8 type. Moreover, the NTS1, NTS2, and NTS8 strains were isolated from geographically distant areas of Japan (Fig.…”
Section: Structure Of the Nts Regionsmentioning
confidence: 99%
“…However, in 1997, the first isolates of A. benhamiae were cultured from a rabbit in Japan (5). The strains isolated from a family with human dermatophytosis and their household pet (a rabbit) in 1996 were later identified as A. benhamiae strains (6). Several isolates of A. benhamiae have since been cultured from human and animal specimens in Japan, and the origins of these strains and the pathway of their dissemination are of epidemiological interest.…”
Section: Introductionmentioning
confidence: 99%
“…Isoliert wurde hier zumeist T. mentagrophytes (39,45), aber auch Microsporum (M.) canis (7,33,43) und in selteneren Fällen M. gypseum (23,34,44). Bei den wenigen Berichten zu Dermatophytosen bei Haustierkaninchen handelt es sich häufig um Fallberichte von Einzeltieren (22,32,34,44,45). Eine Vielzahl von Faktoren werden als begünstigend für die Entwicklung einer Dermatophytose bei Kaninchen diskutiert (8,15), Studien zur Dermatophytose bei Haustierkaninchen gibt es aber nicht.…”
Section: Introductionunclassified